Sistem Kontrol Optimal Fuzzy-Particle Swarm Optimization: (Studi Kasus Pada Model Kendaraan Dengan Steer By Wire System) - Fachrudin Hunaini; Imam Robandi; Nyoman Sutantra (Jurnal Intake : Jurnal Penelitian Ilmu Teknik dan Terapan, 2018)
Fuzzy Logic Control (FLC) is a reliable control system for controlling nonlinear systems, but to obtain optimal fuzzy logic control results, optimal Membership Function parameters are needed. Therefore in this paper Particle Swarm Optimization (PSO) is used as a fast and accurate optimization method to determine Membership Function parameters. The optimal control system simulation is carried out on the automatic steering system of the vehicle model and the results obtained are the vehicle’s lateral motion error can be minimized so that the movement of the vehicle can always be maintained on the expected trajectory